Guest satisfaction survey on public bus services: a case study in Kuantan - Aneesa Aqeela, Mohd Asha’ari (2016)
Public transport is a shared passenger transport service which is available for all people. Thousands of people use the public bus around Kuantan to reach their destinations. Nevertheless, increasing private vehicles on major roads in Malaysia have created problems in traffic congestion which further make accidents, air and noise pollution. The public also refused that the busses’ poor condition and the irregular and unpleasant services. Therefore, this study is intended to explore demographic behaviour of passenger public bus services and assess passenger satisfaction. At the same time, the survey also was conducted to evaluate passenger loyalty. To achieve this objective, Kuantan city has been chosen as a study area namely Rapid Kuantan Bus Station, Terminal Sentral Kuantan, Urban Transformation Centre (UTC) and University Malaysia Pahang. A total of 150 questionnaires were collected. Then, the average index method was performed to evaluate customer satisfaction. While to indicate customer loyalty Net Promoter Score method was chosen. The result demonstrates that, the user was satisfied on public bus. However, a possibility person to use other services is detractor. This means that people will use other services such as cab, trail and other things. Thus, the improvement of the service quality of public bus transport is important sign to makes it up since, the public bus transport one is majority of the public bus transport in Kuantan.